Analysis of endocrine activity in drinking water, surface water and treated wastewater from six countries. (1st August 2018) - Leusch, Frederic D.L.; Neale, Peta A.; Arnal, Charlotte; Aneck-Hahn, Natalie H.; Balaguer, Patrick; Bruchet, Auguste; Escher, Beate I.; Esperanza, Mar; Grimaldi, Marina; Leroy, Gaela; Scheurer, Marco; Schlichting, Rita; et al.
Abstract: The aquatic environment can contain numerous micropollutants and there are concerns about endocrine activity in environmental waters and the potential impacts on human and ecosystem health. In this study a complementary chemical analysis and in vitro bioassay approach was applied to evaluate endocrine activity in treated wastewater, surface water and drinking water samples from six countries (Germany, Australia, France, South Africa, the Netherlands and Spain). The bioassay test battery included assays indicative of seven endocrine pathways, while 58 different chemicals, including pesticides, pharmaceuticals and industrial compounds, were analysed by targeted chemical analysis. Endocrine activity was below the limit of quantification for most water samples, with only two of six treated wastewater samples and two of six surface water samples exhibiting estrogenic, glucocorticoid, progestagenic and/or anti-mineralocorticoid activity above the limit of quantification. Based on available effect-based trigger values (EBT) for estrogenic and glucocorticoid activity, some of the wastewater and surface water samples were found to exceed the EBT, suggesting these environmental waters may pose a potential risk to ecosystem health. In contrast, the lack of bioassay activity and low detected chemical concentrations in the drinking water samples do not suggest a risk to human endocrine health, with all samples below the relevant EBTs. Graphical abstract: Highlights: Wastewater, surface water and drinking water grab samples from 6 countries analysed. Applied bioassays for 7 endocrine pathways in agonist and antagonist mode. Endocrine activity only above LOQ in two wastewater and two surface water samples. Estrogenic and glucocorticoid activity in wastewater may pose ecological risk. Lack of endocrine activity in drinking water indicates negligible risk to humans.